CHALLENGES IN FLUID MANAGEMENT OF AN END-STAGE RENAL DISEASE PATIENT WITH COVID-19 PNEUMONIA AND STARVATION KETOACIDOSIS - Chyi, Tan Yan; Adam, Ida Ilyani (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Fluid management is a delicate process when it involves an anuric end-stage renal disease (ESRD) patient on regular hemodialysis, who has Coronavirus Disease-19 (COVID-19) pneumonia in acute respiratory distress syndrome (ARDS). The management is made even more challenging when the condition of the patient is complicated with starvation ketoacidosis. There is limited literature with regards to this issue. CASE We report the case of a 55-year-old male patient with ESRD, who is suffering from COVID-19 pneumonia in ARDS with concomitant starvation ketoacidosis. CONCLUSION Starvation ketoacidosis is an under-recognized cause of metabolic acidosis and may occur even in a diabetic patient who has been acutely unwell with poor oral intake. While the mainstay of therapy in a patient with starvation ketoacidosis is to provide an intravenous dextrose-containing fluid replacement, this has to be judiciously given in an anuric ESRD patient on fluid restriction. A careful balance between low-dose insulin infusion to maintain euglycemia and strict fluid management is crucial to stop gluconeogenesis and ketogenesis. The ultimate goal is to bring the patient out of starvation ketoacidosis while avoiding the deleterious effect of fluid overload in a patient who is already in ARDS.